Bāpunā patro : Saradāra Vallabhabhāīne, 8-7-'21 thī 29-12-'47 - Gandhi, Mahatma, 1869-1948 (SAMP early 20th-century Indian books project, 1952)
Letters written to Vallabhbhai Patel, 1875-1950, Indian statesman.